Feasibility and Safety of High-Risk Percutaneous Coronary Intervention Without Mechanical Circulatory Support. (7th June 2021) - Khalid, Nauman; Rogers, Toby; Torguson, Rebecca; Zhang, Cheng; Shea, Corey; Shlofmitz, Evan; Chen, Yuefeng; Musallam, Anees; Wermers, Jason P.; Case, Brian; Hashim, Hayder; Ben-Dor, Itsik; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Recommendations to broaden the use of mechanical circulatory support (MCS) for high-risk percutaneous coronary intervention (PCI) remain controversial with the absence of robust evidence from randomized clinical trials and the risk of device-related complications. This investigation examined whether performing high-risk PCI without elective MCS is feasible and safe. Methods: We performed a single-center, retrospective analysis for patients meeting contemporary high-risk PCI criteria as defined by the Interventional Council of the American College of Cardiology. These criteria include unprotected left main disease, last remaining conduit, left ventricular ejection fraction <35%, three-vessel coronary artery disease, severe aortic stenosis, or severe mitral regurgitation. Clinical, procedural, and major in-hospital and 30-day cardiovascular outcomes were assessed. Results: The analysis included a cohort of 1680 patients (2887 lesions) with stable coronary artery disease who met high-risk PCI criteria and were treated from 2003 to 2018. The study population comprised 75% men and 68% whites. Mean age was 69.16±11.19 years. Conventional cardiovascular risk factors among our cohort were as follows: hypertension, 91%; hypercholesterolemia, 91%; diabetes, 44%; and cigarette smoking, 14%. Intravascular ultrasound was performed on 53% of the lesions. Rescue MCS was required in 0.8% of the patients. Procedural success was observed in 98.2% of the patients, while the 30-day mortality rate was 1.6%. The incidence of major complications was as follows: all-cause mortality, 1.6%; cardiac death, 0.8%; acute renal failure, 4.6%; stroke, 0.2%; and major bleeding, 1.1%. Conclusions: High-risk PCI as defined by the professional societies without elective MCS is feasible and safe in the majority of patients, challenging the current recommendations and practice. A randomized trial comparing unprotected versus protected high-risk PCI for these broad recommendations is warranted to best ascertain which patients would benefit from MCS.